Carbon Capture and Storage in Developing Countries : A Perspective on Barriers to Deployment - Kulichenko, Natalia; Ereira, Eleanor (Washington, DC: World Bank, 2012)
This report assesses some of the most important barriers facing Carbon Capture and Storage (CCS) deployment within the context of developing and transition economies. The selection of the case studies is based on several criteria, including the level of reliance on fossil fuels for power generation and the level of interconnection of electricity networks. The case studies selected for this analysis are the Balkans and Southern African regions. Many countries within the Balkan region are considered transition economies, a status recognized as different from middle-income and low income developing countries. However, for the purposes of this report, countries within both regions are referred to as developing countries. The report presents the results of a model developed to investigate ways of structuring financing for power generation facilities equipped with CCS in the developing world, using instruments available from multilateral development banks and commercial financiers, as well as concessional funding sources. The objective is to assess whether a combination of such instruments could result in reductions in the overall cost of financing. The model calculates the resulting Levelized Cost of Electricity (LCOE), and includes numerous variable parameters, such as coal prices, CO2 prices, and potential revenues from selling oil and gas obtained through enhanced hydrocarbon recovery. Common theme found throughout the analyses is that there could be potential for CCS deployment in the regions under consideration. Lower-cost opportunities, for example, in sectors practiced in handling CO2, such as gas processing, or where extra revenues could be made available from enhanced hydrocarbon recovery, could provide platforms for the first CCS projects in developing countries. However, broader CCS deployment is contingent upon a number of factors, including an availability of a mix of sources of finance from public funds and carbon market mechanisms, as well as concessional financing sources. In parallel, financing should be supported by legal and regulatory frameworks not only to define mechanisms for access to concessional and climate finance, but also to reduce investor risk and create market drivers to leverage all available sources of domestic and international support.